Fecal Microbial Diversity and Structure Are Associated with Diet Quality in the Multiethnic Cohort Adiposity Phenotype Study. Issue 9 (12th June 2019) - Maskarinec, Gertraud; Hullar, Meredith A J; Monroe, Kristine R; Shepherd, John A; Hunt, Jeani; Randolph, Timothy W; Wilkens, Lynne R; Boushey, Carol J; Le Marchand, Loïc; Lim, Unhee; Lampe, Johanna W
ABSTRACT: Background: Variation in gut microbial community structure is partly attributed to variations in diet. A priori dietary indexes capture diet quality and have been associated with chronic disease risk. Objectives: The aim of this study was to examine the association of diet quality, as assessed by the Healthy Eating Index, Alternative Healthy Eating Index-2010, alternate Mediterranean Diet, and the Dietary Approaches to Stop Hypertension Trial, with measures of fecal microbial community structure assessed in the Adiposity Phenotype Study (APS), an ethnically diverse study population with varied food intakes. Methods: Multiethnic Cohort Study members completed a validated quantitative food frequency questionnaire (QFFQ) at cohort entry (1993–1996) and, for the APS subset, at clinic visit (2013–2015), when they also provided a stool sample. DNA was extracted from stool, and the V1-V3 region of the 16S rRNA gene was amplified and sequenced. Dietary index scores were computed based on the QFFQ and an extensive nutritional database. Using linear regression adjusted for relevant covariates, we estimated associations of dietary quality with microbiome measures and computed adjusted mean values of microbial measures by tertiles of dietary index scores. Results: The 858 men and 877 women of white, Japanese American, Latino, Native Hawaiian, and African American ancestry had a mean age of 69.2 years at stool collection. Alpha diversity according to the Shannon index increased by 1–2% across tertiles of all 4 diet indexes measured at clinic visit. The mean relative abundance of the phylum Actinobacteria was 13–19% lower with higher diet quality across all 4 indexes (difference between tertile 3 and tertile 1 divided by tertile 1). Of the 104 bacterial genera tested, 21 (primarily from the phylum Firmicutes ) were positively associated with at least 1 index after Bonferroni adjustment. Conclusion: Diet quality was strongly associated with fecal microbial alpha diversity and beta diversity and several genera previously associated with human health.